UPAYA MENINGKATKAN MOTIVASI BELAJAR SEJARAH INDONESIA SISWA MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE STAD BERBANTUAN FILM DOKUMENTER DI SMA NEGERI 5 TEBO TAHUN PELAJARAN 2017/2018 - DARMI DARMI (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2022)
The purpose of this study was to determine the application of the Student Teams Achievment Division (STAD) cooperative learning model with the documentary film of the Japanese occupation in Indonesia in learning Indonesian history in increasing learning motivation and historical awareness of students in class XI MIPA-1 SMA Negeri 5 Tebo, Tebo Regency, Jambi Province. The method used is classroom action research (CAR). The research data were obtained from observations of learning activities, informants (students, teachers, and school principals), documents, and photos of activities with the stages of planning, action, observing, and reflecting. This research was conducted in three cycles. The results showed an increase achieved by students in the first cycle for the attitude of learning motivation an average of 67.9, the second cycle increased 76.66, and the third cycle reached 83.11. For the students' historical awareness attitude, the average of the first cycle was 68.8, the second cycle increased 79.4, and the third cycle increased 85.05. Furthermore, the increase in student achievement or learning outcomes is seen from the average post-test, namely the first cycle of 69.5, an increase of 74.42, and an increase of 79.8 in the third cycle. With the percentage of classical completeness in the first cycle of 42.85%, the second cycle increased by 60%, and the third cycle increased by 85.71%. Minimum Completeness Criteria (KKM) History is 75 with a minimum percentage of classical completeness determined at 75%. Percentage of Classical Completeness At a minimum, the scale of learning motivation and historical awareness is 80%. ABSTRAKTujuan penelitian ini untuk mengetahui penerapan model pembelajaran kooperatif tipe Student Teams Achievment Division (STAD) dengan film documenter pendudukan Jepang di Indonesia dalam pembelajaran sejarah Indonesia dalam meningkatkan motivasi belajar dan kesadaran sejarah siswa kelas XI MIPA-1 SMA Negeri 5 Tebo Kabupaten Tebo Provinsi Jambi. Metode yang digunakan adalah penelitian tindakan kelas (PTK). Data penelitian diperoleh dari pengamatan kegiatan pembelajaran, informan (siswa, guru, dan kepala sekolah), dokumen, dan foto kegiatan dengan tahapan planning, action, observing, dan reflecting. Penelitian ini dilaksanakan dalam tiga siklus. Hasil penelitian menunjukan adanya peningkatan yang dicapai siswa pada siklus I untuk sikap motivasi belajar ratarata 67,9, siklus II meningkat 76,66, dan siklus III mencapai 83,11. Untuk sikap kesadaran sejarah siswa memperoleh rata-rata siklus I 68,8, siklus II meningkat 79,4, dan siklus III mengalami peningkatan 85,05. Selanjutnya, peningkatan prestasi atau hasil belajar siswa dilihat dari rata-rata post test yakni siklus I 69,5 meningkat 74,42, dan pada siklus III meningkat 79,8. Dengan persentase ketuntasan klasikal siklus I 42,85%, siklus II meningkat 60%, dan siklus III meningkat 85,71%. Kriteria Ketuntasan Minimal (KKM) Sejarah adalah 75 dengan persentase ketuntasan klasikal minimal ditentukan 75%. Persentase Ketuntasan Klasikal Minimal skala sikap motivasi belajar dan kesadaran sejarah adalah 80%.